A West African Middle Stone Age site dated to the beginning of MIS 5: Archaeology, chronology, and paleoenvironment of the Ravin Blanc I (eastern Senegal). Issue 154 (May 2021) - Douze, Katja; Lespez, Laurent; Rasse, Michel; Tribolo, Chantal; Garnier, Aline; Lebrun, Brice; Mercier, Norbert; Ndiaye, Matar; Chevrier, Benoît; Huysecom, Eric
Abstract: The Ravin Blanc I archaeological occurrence, dated to MIS 5, provides unprecedented data on the Middle Stone Age (MSA) of West Africa since well-contextualized archaeological sites pre-dating MIS 4/3 are extremely rare for this region. The combined approach on geomorphology, phytolith analysis, and OSL date estimations offers a solid framework for the MSA industry comprised in the Ravin Blanc I sedimentary sequence. The paleoenvironmental reconstruction further emphasizes on the local effects of the global increase in moisture characterizing the beginning of the Upper Pleistocene as well as the later shift to more arid conditions. The lithic industry, comprised in the lower part of the sequence and dated to MIS 5e, shows core reduction sequences among which Levallois methods are minor, as well as an original tool-kit composition, among which pieces with single wide abrupt notches, side-scrapers made by inverse retouch, and a few large crudely shaped bifacial tools. The Ravin Blanc I assemblage has neither a chronologically equivalent site to serve comparisons nor a clear techno-typological correspondent in West Africa. However, the industry represents an early MSA technology that could either retain influences from the southern West African 'Sangoan' or show reminiscences of the preceding local Acheulean. A larger-scale assessment of behavioral dynamics at work at the transition period between the Middle to Upper Pleistocene is discussed in view of integrating this new site to the global perception of this important period in the MSA evolutionary trajectories.